Discontinuous splenogonadal fusion diagnosed on computed tomography - Jakkani, Ravikanth (Indian J Radiol Imaging, 2016)
Splenogonadal fusion is a very rare congenital anomaly which often manifests as a scrotal mass and rarely as cryptorchidism. It can be of continuous and discontinuous type based on the presence of a band of connecting splenic tissue. We report a rare case of discontinuous type of splenogonadal fusion in an adolescent male presenting as cryptorchidism. We emphasize the computed tomographic findings, which helped us in preoperative diagnosis and aided in appropriate management.